YUNUS RAJABI’S ACTIVITY IN NOTATING SHASHMAKOM: SCIENTIFIC-PRACTICAL MECHANISMS OF PRESERVING NATIONAL MUSICAL HERITAGE - Shonazarova Mahbuba Abdunabi qizi (International Journal of Literature and Language Studies, 2026)
This article examines the scientific and practical contribution of Academician Yunus Rajabi to the notation of Shashmaqom. The study employs historical-musicological, comparative, and source-analysis methods. The findings demonstrate that Rajabi’s notation activities played a crucial role in preserving, systematizing, and transmitting the musical texts of Shashmaqom to future generations. The research highlights the significance of his work in the development of Uzbek maqom art and the safeguarding of intangible cultural heritage. Furthermore, the scientific and practical mechanisms of Shashmaqom notation are systematized and their importance for contemporary maqom studies is discussed.